Transformational Leadership as a Catalyst for Effective Administrative Services - Putri, Arnisyah; Jamaluddin, Jamaluddin; Isgunandar, Isgunandar; Rahman, Nawir (Journal of Public Policy and Local Government (JPPLG), 2025)
More effective and efficient administrative services could be influenced by employee performance. Organizations place a great deal of importance on performance since it can undoubtedly lower absenteeism and lazy work. The purpose of this study is to determine the impact of transformational leadership, the impact of leadership on employee performance, and the overall picture of employee performance. This study employs associative research design and a quantitative methodology. To accomplish the goals of this study, a variety of data-gathering methods were employed, such as documentation, questionnaires, and observation. The study's population consists of 95 employees, and a sample of 48 employees was drawn using the proportional random sampling sample extraction approach. To ascertain the impact of transformational leadership on staff performance at the South Sulawesi Province Teacher Mobilization Center (BBGP) office, the research data was further analyzed using descriptive and inferential statistical analysis. The study's findings demonstrated that the indicators applied to each variable concluded that both employee performance and the impact of transformational leadership fell into a very good range. The product moment correlation test findings indicate a strong link between the variables. Transformational leadership significantly improved staff performance in the South Sulawesi Province Teacher Mobilization Center (BBGP) office, according to the findings of a basic linear regression analysis.